2004
DOI: 10.1210/jc.2003-030723
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Adipocyte, Free Fatty Acids, and Ectopic Fat in Pathogenesis of Type 2 Diabetes Mellitus: Peroxisomal Proliferator-Activated Receptor Agonists Provide a Rational Therapeutic Approach

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by insulin resistance in liver and muscle and impaired insulin secretion. Considerable evidence also implicates deranged adipocyte metabolism and altered fat topography in the pathogenesis of glucose intolerance in T2DM. 1) Fat cells are resistant to insulin's antilipolytic effect, leading to day-long elevated plasma FFA levels. Chronically increased plasma FFA stimulates gluconeogenesis, induces hepatic/muscle insulin resistance, and impairs insulin secretion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
454
2
34

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 581 publications
(508 citation statements)
references
References 301 publications
(171 reference statements)
18
454
2
34
Order By: Relevance
“…Consistent with previous studies in man [16][17][18][19]35], PIO in the present study enhanced adipocyte sensitivity to the antilipolytic effect of insulin, leading to a decrease in fasting plasma NEFA concentration and improved insulinmediated suppression of plasma NEFA concentration. These results are consistent with the concept that the insulin-sensitising effect of PPAR-γ agonists, at least in part, are indirect and mediated via a reduction in plasma NEFA and intramyocellular concentration of toxic lipid metabolites [1,35]. In a recent study [36], PIO was shown to enhance the clearance of very-low-density-lipoprotein (VLDL) triacylglycerol-rich particles from the circulation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with previous studies in man [16][17][18][19]35], PIO in the present study enhanced adipocyte sensitivity to the antilipolytic effect of insulin, leading to a decrease in fasting plasma NEFA concentration and improved insulinmediated suppression of plasma NEFA concentration. These results are consistent with the concept that the insulin-sensitising effect of PPAR-γ agonists, at least in part, are indirect and mediated via a reduction in plasma NEFA and intramyocellular concentration of toxic lipid metabolites [1,35]. In a recent study [36], PIO was shown to enhance the clearance of very-low-density-lipoprotein (VLDL) triacylglycerol-rich particles from the circulation.…”
Section: Discussionsupporting
confidence: 86%
“…Although PPAR-α-null mice do not manifest any obvious alteration in insulin sensitivity [42], PPAR-α activation in nutritional (high-fat diet), genetic (Zucker obese fa/fa rat), and lipoatrophic (A-ZIP/ F-1) models of insulin resistance markedly improves insulin sensitivity [4,7,43] and reduces visceral fat in the two former models. Intracellular fatty acids and their derivatives interfere with insulin-stimulated glucose metabolism, through an effect on the insulin-signalling pathway, possibly by activating protein kinase C [1,44]. In rodents it has been suggested that PPAR-α activation increases fatty acid oxidation, thus decreasing intramyocellular lipid content and improving insulin sensitivity [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In insulin-resistant states, signal transduction via the insulin receptor (IR) 2 is impaired with decreased activation of downstream obligate molecular intermediates, such as IRS-1, Akt, and PKC (1), that are involved in stimulating translocation of GLUT4 proteins to the cell surface.…”
mentioning
confidence: 99%
“…Many factors have been reported to induce insulin resistance in vitro and in vivo, including lipid-and fat-derived free fatty acids (FFAs) (2). Lipid infusion and high fat feeding promote insulin-resistant states in rodents (3) and humans (4,5), and elevated plasma FFA concentrations typically correlate with obesity and decreased target tissue insulin sensitivity in humans.…”
mentioning
confidence: 99%